Comment on "A computational technique to classify several fractional Brownian motion processes" [Chaos Solitons and Fractals 150(2021) 111152]. (August 2022) - Wang, Bichen; Hou, Yulei
Abstract: In the paper by Mahmoudi MR[Chaos Solitons and Fractals 150(2021) 111152], fractional Brownian motion B H ( t ) is defined by Riemann Liouville integral and the covariance for B H ( t ) is given. Through a proposition we show that the covariance for B H ( t ) in mentioned paper is incorrect.